Intellectual Properties of a Sui Generis Nature: Traditional Knowledge of the Agricultural Sector. International Protection - Acea Valdés, Yeney (DIXI, 2015)
Topic and scope: Traditional knowledge consists of wisdom and experiences transmitted between generations, or which stem from processes of creation and experimentation. The variety of this knowledge is indicative of the complexity involved in its legal recognition. Characteristics: At this level, traditional knowledge of agriculture constitutes precious immaterial goods. Thy are undoubtedly the necessary and imperative solution for scarcity or lack of resources. Thy are also related to other categories such as environmental sustainability and global development, elements that increase in importance and value in modern times. Conclusions: Th epicenter of this article is the analysis of traditional agricultural knowledge. In this regard, the institution is characterized as a function of its conceptual defiition and legal nature. With equal emphasis, the current system for protection in the framework of international bodies and instruments is evaluated.